Indústria Cinematográfica - A Gestão do Cinema no Brasil - COSTA, Thyago Wagner de Almeida (172, 2023)
Cinema siginifica arte e cultura e também é considerado uma atividade econômica que fatura bilhões de dólares em todo mundo e movimenta um contingente enorme de profissionais de criação, produção e distribuição. O artigo cientifico “Indústria Cinematográfica - Gestão do Cinema Nacional” é um trabalho acadêmico que busca os desafios e entendimentos sobre as fases do audiovisual brasileiro, estudando suas particularidades de época e seus avanços até os dias atuais. No decorrer do artigo, será desenvolvido uma compreensão sobre o impacto da democratização cultural para auxiliar na formação intelectual de indivíduos.

Cinema means art and culture and is also considered an economic activity that earns billions of dollars worldwide and involves a huge contingent of creative, production and distribution professionals. The scientific article “Cinematic Industry - Management of National Cinema” is an academic work that seeks challenges and understandings about the phases of Brazilian audiovisual, studying its particularities at the time and its advances to the present day. Throughout the article, an understanding of the impact of cultural democratization will be developed to assist in the intellectual formation of individuals.
Keywords: Cultura; Cinema; Gestão e Negócios